2006
DOI: 10.1590/s0102-76382006000200016
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento endovascular dos aneurismas de aorta abdominal: experiência inicial e resultados a curto e médio prazo

Abstract: Tratamento endovascular dos aneurismas de aorta abdominal: experiência inicial e resultados a curto e médio prazo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
6
0
3
Order By: Relevance
“…In Brazil, the effort of the Brazilian Society of Cardiovascular Surgery to report on and guide about this disease has steadily improved treatment [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the effort of the Brazilian Society of Cardiovascular Surgery to report on and guide about this disease has steadily improved treatment [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the patients have been classified as moderate risk for per-operative cardiac complications, as expected by their main disease and co-morbidities [11,20]. Patients showed a moderate surgical risk, and they have been in accordance with the estimated cardiac risk obtained by applying the Goldman scale.…”
Section: Fig 2 -Correlations Between Plasmatic Arginine-vasopressin mentioning
confidence: 95%
“…Since they have favorable anatomy, endovascular treatment has recommendation grade "A" in these cases. In our environment, Saadi et al [9] reported a series of 25 patients undergoing endovascular repair of abdominal aortic aneurysm with 96% of patients alive and free of further intervention, up to a 27-month follow-up period.…”
Section: Fig 2 -Thrombosed False Lumem Of the Ascending Aortic Arch mentioning
confidence: 99%